In the name of employability: Faculties and futures for the arts and humanities in higher education. (April 2023) - Ashton, Daniel; Bennett, Dawn; Bulaitis, Zoe Hope; Tomlinson, Michael
This introductory overview sets out the scope and aims of the special issue, which is concerned with establishing more meaningful understandings and discourses on the relationship between arts and humanities and graduate employability. The issue comes at a time of increased government-level questioning of the social and economic value of higher education (HE), and particularly humanities disciplines. The propositions developed in this introduction and the contributing authors' papers aim towards developing stronger and more meaningful engagement with the future place and role of arts and humanities within HE and wider society. We establish a variety of themes in the value of HE and make connections to the contributing authors' articles. We finish with critical questions for continued debate and research in the nexus between arts and humanities and graduate outcomes. These are all pertinent to the questions of value that underpin many of the papers in this issue.